The Role of Complement in Tumors - Rolfe, Barbara; Pio, Ruben; Woodruff, Trent M.; Markiewski, Maciej M.; Manthey, Helga D. (Frontiers Media SA, 2020)
The complement system is an essential part of the innate immune system that is responsible for regulating inflammation, facilitating immune defense mechanisms, and maintaining tissue homeostasis. Despite its critical role in the regulation of immunity, the complement system has also been implicated in the pathogenesis of a range of inflammatory diseases, including cancer. The complement system can eliminate tumor cells via complement-dependent cytotoxicity and antibody-dependent cell-mediated cytotoxicity. In turn, cancer cells are thought to evade complement-mediated destruction by up-regulating the expression of endogenous complement inhibitors. However research over the past 10 years has demonstrated that complement proteins, in particular the complement anaphylatoxins C3a and C5a, contribute to tumor growth and metastasis. Complement proteins have been shown to also promote tumor growth indirectly, either via host immune cells to promote an immunosuppressive microenvironment or via vascular cells to promote angiogenesis. However these proteins may also affect tumor cells directly by contributing to genetic instability and by promoting tumor growth and metastatic spread. This Research Topic gives an overview of the role of complement proteins in regulating tumor development, progression and metastasis. In addition, it provides perspectives on the potential targeting of complement in cancer therapy.